Pengaruh Kesadaran Wajib Pajak, Pengetahuan dan Pemahaman Perpajakan Terhadap Kepatuhan Wajib Pajak di Kota Semarang - Eko Andi Riyanto; Tri Widyastuti Ningsih (Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to analyze the factors that influence the level of compliance of individual taxpayers in the city of Semarang. The independent variables used to test the level of individual taxpayer compliance are taxpayer awareness, knowledge and understanding of taxation. Respondents in this study were individual taxpayers registered based on the SPT and domiciled in the city of Semarang. The sampling technique in this study used the proportional cluster random sampling method, where the data source was primary data obtained from the distribution of questionnaires as research instruments. Data analysis used multiple linear regression with the help of SPPS version 23 for windows. The results of the study indicate that: 1) Taxpayer awareness has a positive and significant impact on the level of individual taxpayer compliance; 2) Knowledge and understanding of taxation has a positive and significant impact on the level of compliance of individual taxpayers; 3) Taken together, taxpayer awareness, knowledge and understanding of taxation have a positive and significant impact on the level of individual taxpayer compliance.